Alarm fatigue: impacts on patient safety. Issue 6 (December 2015) - Ruskin, Keith J.; Hueske-Kraus, Dirk
Abstract : Purpose of review: Electronic medical devices are an integral part of patient care. As new devices are introduced, the number of alarms to which a healthcare professional may be exposed may be as high as 1000 alarms per shift. The US Food and Drug Administration has reported over 500 alarm-related patient deaths in five years. The Joint Commission, recognizing the clinical significance of alarm fatigue, has made clinical alarm management a National Patient Safety Goal. Recent findings: Potential solutions to alarm fatigue include technical, organizational, and educational interventions. Selecting only the right monitors (i.e., avoiding overmonitoring), judicious selection of alarm limits, and multimodal alarms can all reduce the number of nuisance alarms to which a healthcare worker is exposed. Summary: Alarm fatigue can jeopardize safety, but some clinical solutions such as setting appropriate thresholds and avoiding overmonitoring are available.